Occupational therapy-Work assessment and preparation - Mary-Ann Jack-Bleach (South African Journal of Physiotherapy, 1983)
This paper presents aspects of the role of the occupational therapist in the assessment and preparation of patients for work. The roles of the occupational therapist in working with two broad categories of workers, viz. the worker in industry who is experiencing problems related directly or indirectly to his work situation, and the disabled person who wishes to work, are described.